OPTIMIZATION OF TRANSPORT HUBS AT URBAN RAILWAY STATIONS CONSIDERING PASSENGER FLOW DYNAMICS - Stepanchuk, Oleksandr; Chernyshova, Oksana (Theory and practice of design, 2025)
The article addresses the issues related to the operation of transport hubs (THs) at urban railway stations, including the uneven distribution of passenger flows, inefficient spatial planning, and insufficient coordination between different modes of transport. The study examines the impact of urban, technological, and infrastructural factors on the efficiency of transport hubs and proposes approaches for their optimization, taking into account the dynamics of passenger flows. The aim is to develop scientifically grounded methods for optimizing the parameters of transport hubs based on the analysis of passenger flow dynamics, taking into account the constraints related to urban planning, economic, and social conditions of station operation. The methodology is based on the analysis of contemporary scientific research, mathematical modeling of passenger flows, and the assessment of the impact of urban planning and transport solutions on the functioning of the hubs. Results. The study identified key patterns and characteristics of the operation of transport hubs at railway stations in the context of urbanization, technological development, and social challenges. It was established that flexible planning of transport hubs, considering digital integration, adaptive architecture, and passenger-centric design, significantly enhances transfer efficiency, user comfort, and safety. The necessity of a comprehensive approach to optimizing transport hub parameters was substantiated, taking into account pedestrian flow dynamics, seasonal and event-driven fluctuations, as well as emergency scenarios. The proposed model contributes to the creation of a more efficient, sustainable, and user-oriented urban transport infrastructure. Scientific novelty. The scientific novelty of the study lies in the development of a universal approach to transport hub optimization, which combines passenger flow analysis, infrastructure design, and digital platform integration. This approach enables station complexes to adapt to changing operational conditions and predict future demand. Practical relevance. The practical significance of the article is that it offers scientifically grounded approaches to optimizing transport hubs at railway stations, which can be directly applied in urban planning and transport management. The proposed solutions enhance the efficiency of passenger flow organization, reduce transfer times, and improve comfort and safety for users. Moreover, the research results can be utilized in the design of new or the reconstruction of existing station complexes, as well as in the development of sustainable urban development strategies.